Dynamical Behavior of Two Dimensional Hénon Maps (Bangladesh Journal of Scientific and Industrial Research, 2012)
In this article, we study the two dimensional non-linear dynamical behavior of Hénon maps. We investigate the parameter values for which fixed points and periodic points of period two exist and study the dimension of the maps. We also investigate the numerical results of the maps and use computer programming Mathematica for generating graphs and computations. DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10722 Bangladesh J. Sci. Ind. Res. 47(1), 55-60, 2012